Titanium elastic nailing system of diaphyseal femur fracture in a 7 years old child: a case report - Tarmalinggam, Shangeetha; Appasamy, Edzell Swamy; Abdul Ghani, Kamarul Al-Haqq; Kamisan, Norazian (Lycia Press London UK, 2022)
Objective: Midshaft femur fracture commonly treated conservatively in paediatric patients. However, complications are seen in conservative treatments and lately surgical interventions are being practised tremendously to minimise the complications. Case Report: A 7 years old boy, sustained a closed fracture midshaft left femur after a motor vehicle accident. Operative management was decided for this patient using Titanium Elastic Nailing System, which revealed a good outcome within 3 months of duration. Conclusion: Titanium Elastic Nailing System is fixed with minimally invasive techniques in children 6-16 years of age with diaphyseal femoral fractures, which gives a good outcome and minimizes the complications and allows earlier rehabilitation and return to school life by speeding up the fracture healing. However, an experienced surgeon and good surgical technique is desired to minimize the complications that may occur.